The economic and public health impact of influenza vaccinations: contributions of Swiss pharmacies in the 2016/17 and 2017/18 influenza seasons and implications for vaccination policy (Swiss Medical Weekly, 2019)
AIMS OPF THE STUDY Healthy adults have had the option to receive prescriptionless vaccination against influenza in pharmacies of several Swiss cantons since the 2015/16 influenza season. We aimed to assess in a cost-benefit analysis the resulting net benefits for the Swiss economy and public health, and the benefits that could be expected if an extension of the current vaccination recommendations was implemented. METHODS The proportion of influenza vaccines administered in pharmacies was calculated from data provided by pharmacies entering information in phS-net.ch, data from vaccines covered by insurance companies, and vaccine supply data. The economic and public health impact was estimated in a cost-benefit analysis based on published data. RESULTS In the 2016/17 and 2017/18 influenza seasons, 7306 of a total of 1.07 million (0.7%) and 15,617 of a total of 1.15 million (1.4%) influenza vaccine doses, respectively, were administered in pharmacies in Switzerland. The net cost savings for the economy due to vaccination in pharmacies in the 2016/17 and 2017/18 seasons were CHF 66,633 and CHF 143,021, respectively. In the 2017/18 season, this resulted –in a net saving per 100,000 inhabitants of CHF 1918, 94.4 cases of illness, 17.6 visits to primary care physicians, 0.328 hospitalisations, 1.1 hospitalisation days, 0.019 deaths prevented, and 0.353 life-years gained. Influenza vaccination proved to be cost-effective provided that a vaccine efficacy of 59% is exceeded. Extrapolations for the healthy, working-age population revealed that a vaccination coverage rate of 50% and a vaccine efficacy of 70% could save the Swiss economy CHF 18.4 million annually. CONCLUSIONS The service allowing citizens to receive influenza vaccination in Swiss pharmacies is sparsely used. Since influenza vaccination is cost-beneficial as soon as vaccine efficacy surpasses a critical threshold, an extension of the vaccine recommendation for healthy, working-age adults should be considered from an economic point of view.